2018
DOI: 10.1038/s41598-018-31295-8
|View full text |Cite
|
Sign up to set email alerts
|

Na1−xSn2P2 as a new member of van der Waals-type layered tin pnictide superconductors

Abstract: Superconductors with a van der Waals (vdW) structure have attracted a considerable interest because of the possibility for truly two-dimensional (2D) superconducting systems. We recently reported NaSn2As2 as a novel vdW-type superconductor with transition temperature (Tc) of 1.3 K. Herein, we present the crystal structure and superconductivity of new material Na1−xSn2P2 with Tc = 2.0 K. Its crystal structure consists of two layers of a buckled honeycomb network of SnP, bound by the vdW forces and separated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
3
30
1
Order By: Relevance
“…No superconducting transition is observed down to 0.5 K, unlike for Na1-xSn2P2 and NaSn2As2. [17][18][19][20][21] The residual resistivity ratio (300 K)/(0.5 K) is estimated to be 1.3, which is comparable to those of related materials. [13][14][15]17,18,20,21,35 Due to the layered structure of Li1-xSn2+xP2, we investigated its anisotropy in resistivity with respect to uniaxial hot pressing direction above room temperature.…”
Section: Transport Propertiessupporting
confidence: 51%
See 1 more Smart Citation
“…No superconducting transition is observed down to 0.5 K, unlike for Na1-xSn2P2 and NaSn2As2. [17][18][19][20][21] The residual resistivity ratio (300 K)/(0.5 K) is estimated to be 1.3, which is comparable to those of related materials. [13][14][15]17,18,20,21,35 Due to the layered structure of Li1-xSn2+xP2, we investigated its anisotropy in resistivity with respect to uniaxial hot pressing direction above room temperature.…”
Section: Transport Propertiessupporting
confidence: 51%
“…16 It has also been demonstrated that NaSn2As2 and Na1-xSn2P2 show superconducting transitions, meaning that these compounds can also be categorized as novel layered superconductors. [17][18][19][20][21] As well as these ternary-phase materials, the binary tin phosphide Sn4P3 has been investigated as a rechargeable battery anode material. [22][23][24][25][26][27][28][29][30][31] For example, the high reversible capacity of 850 mA•h•g −1 has been achieved for a Na-ion battery with a Sn4P3/C composite anode.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an incorporation of Li or Na into the interlayer space of binary tin phosphides and arsenides resulted in unexpected thermal and superconducting properties. [1][2][3] NaSn2As2 and Na1-xSn2P2 were shown to be superconductors at 1.3 K and 2.0 K respectively, revealing that Sn2Pn2 layers may be a basic layered building block exhibiting superconducting properties. 2,3 In ternary phases, tin atoms are octahedrally coordinated similar to the tin coordination in binary pnictides Sn4P3, Sn4As3, and Sn3P4.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] NaSn2As2 and Na1-xSn2P2 were shown to be superconductors at 1.3 K and 2.0 K respectively, revealing that Sn2Pn2 layers may be a basic layered building block exhibiting superconducting properties. 2,3 In ternary phases, tin atoms are octahedrally coordinated similar to the tin coordination in binary pnictides Sn4P3, Sn4As3, and Sn3P4. 4 Pnictides of lighter tetrels have different structural chemistry due to the tetra-coordinated nature of Si and Ge.…”
Section: Introductionmentioning
confidence: 99%
“…Metal tetrel‐pnictides ( A‐TtPn , A =electropositive metal, Tt =Si, Ge and Sn, Pn =P and As) are a large family of compounds showing a variety of crystal structures and atom connectivity, and exhibiting exciting transport, magnetic, and optical properties [1–9] . The underlying Tt‐Pn anionic sublattice can range from isolated TtPn 4 tetrahedra (Ca 4 SiP 4 , Sr 4 SiP 4 , Ba 4 SiP 4 , Li 8 SiP 4 and Li 8 GeP 4 ), 1D‐chains (Ca 3 Si 2 P 4 and K 2 SiP 2 ), 2D‐layers (LiGe 3 P 3 , LiGe 3 As 3 , Cs 0.16 SiAs 2 , Ca 2 Si 2 P 4 , Li 1‐x Sn 2 As 2 ), to 3D‐frameworks (Li 2 GeP 2 , SrSi 7 P 10 , BaSi 7 P 10 , Li 2 SiP 2 , LiSi 3 As 6 , MgSiAs 2 , Mg 3 Si 6 As 8 , and Ca 3 Si 8 P 14 ) [2,7,10–24] .…”
Section: Introductionmentioning
confidence: 99%